STRATEGI DAKWAH JAMAAH KOPDARIYAH DALAM MERAWAT KEBHINEKAAN - Mazid, Sukron; Prabowo, Wahyu (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2020)
ABSTRACT Kopdariyah Congregation is a cross-generation community that gives color in preaching to create a love of religion, arts and culture so that it is able to care for diversity that is in Magelang raya. The prosecutor must understand the place, culture, habits and language of his object because it determines the success of the Da'wah he did. The research method uses a qualitative descriptive approach through observation, interviews, and documentation. Validity of data via trianggulation (source and method). Data analysis using the Miles and Huberman models are data reduction, data presentation, and conclusion withdrawal. The results of the first research, Model Da'wah Congregation Kopdariyah, (a) discussion party, to give insight and understanding together. (b) Cultural arts, aims to facilitate how to preach giving Syiar. Second, the stage of the preaching of the Kopdariyah Congregation (a) invites, identified the Syiar to be good in life. (b) Embrace, various groups of various cross-denominations, generations and cultures and religions. Keywords: da'wah strategy, diversity